Cardiovascular control in diabetes mellitus. Issue 5971 (14th June 1975) - Bennett, T; Hosking, D J; Hampton, J R
Abstract : Heart rate variability and the changes in heart rate and blood pressure which occur on standing were measured in 21 diabetics. These simple measures distinguished four groups of patients, with loss of parasympathetic activity being commoner than loss of sympathetic activity.